Building the foundation for content success - KOPROWSKI, Gene (EContent, 2006)
Undoubtedly, one trait all publishers today share, whether their origins are print or digital, is a desire to maximize the value of their content, both in facilitating workflow and in providing it in a variety of ways that meet the needs of their customers. During the early 1980s, standards like PostScript, developed by Adobe, were the first wave of specifications for the digital imaging industry. Now new global software standards are emerging for the publishing industry, promising to allow content to do more and make more. However, many publishers are hesitant to embrace these standards despite the potential they offer in easing workflow and enabling content reuse. Screen display illustrations are provided in the article, and a list of companies featured. (Quotes from original text)